FAKTOR-FAKTOR YANG MEMPENGARUHI INTENSITAS PERGERAKAN PEJALAN KAKI DI JALUR PEDESTRIAN KOTA YOGYAKARTA - , RACHMAT WAHYU PRABOWO, ST, Prof. Ir. Bambang Hari Wibisono, MUP., M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The high use of motor vehicles in Yogyakarta has the potential to cause various problems of transportation, environmental, and health. On the other hand, walking mode which has various advantages has not become a priority for the people. The minimal intensity of pedestrians flow in Yogyakarta is assumed due to the low quality of pedestrian. This study attempts to verify such assumption and explore other factors that influence the intensity of pedestrians movements. Field observations and interviews were conducted to obtain data on land-use roads, the quality of pedestrian paths motion comfort, intensity of pedestrian movement (the number of pedestrians per unit time), pedestrians comfort perception, pedestrian characteristic, and pedestrian movement patterns in 4 sample locations. Those 4 sample locations were determined based on differences in the types of its land use, intensity of pedestrian movement, and its road function. Those streets are MT Haryono Street, Sultan Agung Street, P. Diponegoro Street, and Magelang Street. Data analysis used is qualitative methods by comparing the data from four sample sites and then identify whether there is a relationship between land use and motion quality with pedestrian movement convenience and other factors that influence the pedestrian movement in of Yogyakarta. The research indicates the relationship between land use with the intensity of pedestrian movement, the lack of relationship between quality of pedestrian paths motion comforts and pedestrians movement intensity, while other factors which influence pedestrians movement are